2021
DOI: 10.1371/journal.pone.0261974
|View full text |Cite
|
Sign up to set email alerts
|

A ten-year review of indications and outcomes of obstetric admissions to an intensive care unit in a low-resource country

Abstract: Introduction Obstetric intensive care unit admission (ICU) suggests severe morbidity. However, there is no available data on the subject in Ghana. This retrospective review was conducted to determine the indications for obstetric ICU admission, their outcomes and factors influencing these outcomes to aid continuous quality improvement in obstetric care. Methods This was a retrospective review conducted in a tertiary hospital in Ghana. Data on participant characteristics including age and whether participant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In Benin and Mali, Lokossou et al and Samake et al reported complication rates of 10.1% and 13.4%, with case fatality rates of 3.8% and 0.6%, respectively [7] [9]. Higher case fatality rates (5.8% to 26%) have been reported as well [10] [12]. The low rate in our study is related to methodological differences, as these studies were conducted in intensive care units.…”
Section: Prognosismentioning
confidence: 63%
See 2 more Smart Citations
“…In Benin and Mali, Lokossou et al and Samake et al reported complication rates of 10.1% and 13.4%, with case fatality rates of 3.8% and 0.6%, respectively [7] [9]. Higher case fatality rates (5.8% to 26%) have been reported as well [10] [12]. The low rate in our study is related to methodological differences, as these studies were conducted in intensive care units.…”
Section: Prognosismentioning
confidence: 63%
“…Regarding fetal prognosis, the perinatal mortality [8]. Lower rates have been reported in Mali by Samaké (24.60%) [9] and in Ghana by Anane Fenin (25.7%) [10]. Nevertheless, compared to developed countries where obstetric emergencies are low [11], they are frequent and reflect the difficulties of the healthcare system in resource-limited countries [7] [12].…”
Section: Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…1 Primary reasons for pregnant patients requiring admission to an intensive care unit (ICU) include preeclampsia and eclampsia, hemorrhage, cardiovascular conditions, and sepsis. 2 In 2020, a World Health Organization global survey on maternal and newborn health indicated that ICU utilization was associated with a significant reduction in the odds of maternal death and severe maternal morbidity (SMM) among obstetric patients with severe conditions. 3 An obstetric emergency is defined as a condition that necessitates immediate action to prevent SMM or mortality.…”
Section: Introductionmentioning
confidence: 99%
“…However, the United States (US) continues to see a rise in maternal mortality ratio (number of maternal deaths per 100,000 live births) in contrast to what is observed in other industrialized countries 1 . Primary reasons for pregnant patients requiring admission to an intensive care unit (ICU) include preeclampsia and eclampsia, hemorrhage, cardiovascular conditions, and sepsis 2 . In 2020, a World Health Organization global survey on maternal and newborn health indicated that ICU utilization was associated with a significant reduction in the odds of maternal death and severe maternal morbidity (SMM) among obstetric patients with severe conditions 3 …”
Section: Introductionmentioning
confidence: 99%